Cervical subcutaneous emphysema: a rare presentation of pulmonary tuberculosis - Mohammad Nasir, Zuraini; Mohamed, Mohd Hazmi (Pakistan Medical Association, 2019)
Subcutaneous emphysema usually occurs due to direct trauma or iatrogenic injury to the respiratory tract or lungs. We report case of a 64-year-old male with complaint of one-week history of intermittent right neck pain, shortness of breath and fever. Neck examination revealed a diffuse swelling measuring 3x4 cm at right supraclavicular region with presence of crepitus. CT of neck and thorax showed hypodense collection with air pockets along right sternocleidomastoid muscle and multifocal hypodense lung lesion. Diagnosis of pulmonary tuberculosis was confirmed with sputum examination positive for Acid Fast Bacilli (AFB). He was treated with anti-tuberculosis drugs. A CT scan is advocated to assess extension of subcutaneous emphysema and to investigate the causative factor.